The influence of different nanocarriers on skin’s biophysical parameters - Andrade, Sara Catarina Henriques (2017)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017